Maximising Social Value and Health Impact – what is the role of PHIs?. (20th October 2021) - Ashton, K; Green, L; Dyakova, M; Bellis, M
Abstract: Issue: Public health Institutes (PHIs) need to build on traditional approaches to capture and measure their value and impact. As we transfer into the COVID-19 recovery phase, it is important to maximise the value of the health impact but also the social, economic and environmental impact of PHIs. Exploration is required to understand how the social value and impact of PHIs is, or can be, captured and measured. Existing research has illustrated the potential link between Health Impact Assessment (HIA) which assesses health and well-being through the lens of the determinants of health, and economic methods such as Social Return on Investment (SROI). This research aims to understand the current role which PHIs have, in order to strengthen advocacy for investment in public health and prevention in order to protect and improve population health. Description of the problem: A scoping survey was designed and distributed digitally to national and regional PHIs via international networks. Semi-structured interviews were also used to add a qualitative value to the research to allow for triangulation of results. The survey data was analysed descriptively and interview data analysed thematically and coded. Results: The results of the research present an understanding of the meaning of investment, social value and health impact within PHIs including how it is measured using SROI and HIA. It also highlights whether PHIs have considered how capturing social value and health impact can contribute to the recovery from COVID-19, and whether they believe that SROI and HIA have a role in achieving this. Lessons: This innovative work aims to develop a picture of how PHIs are capturing and measuring the wider social, economic and environmental value of their programmes and services. Survey results will be used to help develop a framework for capturing the wider impact and value of public health at an international level, with an aim to achieving sustainable investment in future public health. Key messages: Making the case for investing in public health by illustrating its social, economic and environmental value is vital. Understanding how to capture and measure the wider value of public health is imperative to aid the recovery from COVID-19.